Argentinian potato leafroll virus P0 protein: Novel activities for a previously known suppressor - Barrios Barón, María Pilar (2020)
The potato leafroll virus (PLRV) P0 protein (P0PL) is a suppressor of RNA silencing. In this study, we showed that P0 protein from an Argentinian isolate of PLRV (P0PL-Ar) has an additional activity not described for other PLRV or P0 proteins from poleroviruses. Besides reporting that P0PL-Ar displays both local and systemic silencing suppressor activity, we demonstrated, for the first time, that P0PL-Ar impedes accumulation of dsRNA-derived siRNAs. We also showed that P0PL-Ar interacts with Solanum tuberosum SKP1 orthologue (StSKP1) and triggers destabilization of ARGONAUTE 1 (AGO1) and that these actions are mediated by the F-box-like domain. A mutant in the GW/WG motif within the P0PL-Ar F-box-like motif lost the suppression activity, the interaction with StSKP1 and abolished AGO1 decay. Interestingly, a mutant in the L76/P77 residues within the P0PL-Ar F-box-like motif, which lost the suppression activity and the interaction with StSKP1, retained the capacity to enable AGO1 decay. Thus, unlike other P0 proteins of previously characterized poleroviruses, P0PL-Ar seems to have a dual activity, according to the findings of this study. This protein would act at both an upstream and a downstream step of the RNA silencing pathway: upstream of Dicer-like enzyme (DCL)-mediated primary siRNA production and downstream at the RNA-induced silencing complex (RISC) complex level. Our results contribute to the understanding of the different ways PLRV P0 proteins function as silencing suppressors.